Microcontroller based smart home system / Muhammad Najmi Ahmad @Ahmad Fauzi - Ahmad@Ahmad Fauzi, Muhammad Najmi (2001)
This project report describes the development of a Microcontroller Based Smart Home System. The system can control two type of home appliance, namely light dimmer and fan speed. The system consists of Microcontroller (PIC16F84A), display, keypad, zerocrossing detector circuit, triac circuit, and driver circuit. The control software is written in PIC language and programmed on the PIC controller using MPLAB software. The modules of the system have been tested separately.